2021
DOI: 10.1161/hypertensionaha.120.17646
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial GTPCH (GTP Cyclohydrolase 1) and Tetrahydrobiopterin Regulate Gestational Blood Pressure, Uteroplacental Remodeling, and Fetal Growth

Abstract: Abnormal uteroplacental remodeling leads to placental hypoperfusion, causing fetal growth restriction and pregnancy-related hypertension, which are associated with endothelial dysfunction and markers of reduced vascular NO bioavailability and oxidative stress. Tetrahydrobiopterin (BH4) is a redox cofactor for eNOS (endothelial NO synthase) with a required role in NO generation. Using mice models and human samples, we investigated the physiological requirement for endothelial cell BH4 in uteroplacental vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
(73 reference statements)
3
11
0
Order By: Relevance
“…Consistent with our previous reports (Chuaiphichai et al, 2021), we observed a small but significant increase in basal systolic blood pressure (˜5-7 mmHg) in Gch1 fl/fl Tie2cre mice compared with wild-type littermates (WT: 103 +-2 mmHg, vsGch1 fl/fl Tie2cre mice: 110 +-1 mmHg,P <0.05, n=6; Figure 1A). In wild type mice, systolic blood pressure was unchanged during pregnancy (baseline WT: 103 +-2 mmHg, vs pregnant WT: 103 +-3 mmHg, n=6; Figure 1A).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with our previous reports (Chuaiphichai et al, 2021), we observed a small but significant increase in basal systolic blood pressure (˜5-7 mmHg) in Gch1 fl/fl Tie2cre mice compared with wild-type littermates (WT: 103 +-2 mmHg, vsGch1 fl/fl Tie2cre mice: 110 +-1 mmHg,P <0.05, n=6; Figure 1A). In wild type mice, systolic blood pressure was unchanged during pregnancy (baseline WT: 103 +-2 mmHg, vs pregnant WT: 103 +-3 mmHg, n=6; Figure 1A).…”
Section: Resultssupporting
confidence: 92%
“…The enzyme dihydrofolate reductase (DHFR) reduces dihydrofolate to the fully reduced folate, tetrahydrofolate, and can also reduce oxidized BH2 to regenerate BH4. We have previously demonstrated that supplementation of BH4 with 5-MTHF, restored BH4 levels in pregnancy (Chuaiphichai et al, 2021). In this study we show for the first time that that the combination of BH4 + 5-MTHF is sufficient to restore vascular function in Gch1 fl/fl Tie2cre mice.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations